Forgiveness Predicting Prosocial Behavior In Sundanese Emerging Adults - Fajri Fauzan Azhari; Meida Bella Hanjaswari; Amelia Callista Athoillah; Muhamad Farhan Naufal; Fuad Nashori (IJIP : Indonesian Journal of Islamic Psychology, 2026)
Prosocial behavior plays an important role in maintaining social harmony, particularly in collectivistic cultures such as the Sundanese population. One psychological factor associated with prosocial behavior is forgiveness. This study aims to examine the relationship between forgiveness and prosocial behavior among emerging adults of Sundanese ethnicity. A quantitative correlational design was employed involving 250 participants. Forgiveness was measured using the Forgiveness Scale developed by Nashori, while prosocial behavior was assessed using the Prosocial Behavior Scale by Sefianmi et al. Data were analyzed using Pearson’s product-moment correlation. The results indicated a positive but weak and statistically significant relationship between forgiveness and prosocial behavior (r = 0.196, p = 0.002). These findings suggest that higher levels of forgiveness are associated with higher levels of prosocial behavior. Additionally, forgiveness contributed only 3.86% to the variance in prosocial behavior, indicating that other factors may play a more substantial role in shaping prosocial behavior.